Hand Clap Electronic Control / Farid Syazili Othman and Mohd Khairunizam Mohd Nor - Othman, Farid Syazili; Mohd Nor, Mohd Khairunizam (2002)
Our KEU 380 project is called “ Hand Clap Electronic Control”. We choose this project because it makes our life easy. With this project we don’t have to walk around just to open the switch, we just only have to clap! Circuit operation is as follows. A single handclap will be picked up by the electric microphone, which is coupled through Cl into the op amp 1C 1. The output of 1C1 triggers the 555 IC timers 1C2 that is configured as a monostable multivibrator. The trigger pulse is stretched by IC'2 and gives an output pulse to 1C3 (D flip flop). Because of the three state counter arrangement of 1C3, two sharp claps are required before 1C3 give a high output to Ql, which will turn on KI relay and any device connected to Kl's. Two more claps will give a clock to 1C3 again and will turn off Ql and any device connected to the Kl's.